REPORT OF THE ARCTIC ICE OBSERVING AND FORECASTING PROGRAM-1965. - NAVAL OCEANOGRAPHIC OFFICE WASHINGTON D C (1967)
The ice program conducted primarily in support of 1965 Military Sea Transportation Service arctic operations by the U.S. Naval Oceanographic Office is covered by this report. Methods of collection and dissemination of ice data, ice forecasting, forecast verification, and various allied ice projects are discussed. Ice conditions in the North American Arctic are summarized graphically for 6-day periods from January through December. (Author)